2005
DOI: 10.1109/tbme.2005.846733
|View full text |Cite
|
Sign up to set email alerts
|

Fat and Hydration Monitoring by Abdominal Bioimpedance Analysis: Data Interpretation by Hierarchical Electrical Modeling

Abstract: In a previous publication, it was demonstrated that the abdominal subcutaneous fat layer thickness (SFL) is strongly correlated with the abdominal electrical impedance when measured with a transversal tetrapolar electrode arrangement. This article addresses the following questions: 1) To which extent do different abdominal compartments contribute to the impedance? 2) How does the hydration state of tissues affect the data? 3) Can hydration and fat content be assessed independently? For simulating the measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The idea that transimpedance is influenced by fat content of the mesentery (that is, IAAT) was first suggested by Scharfetter et al (2005). Our study showed a strong relationship between ViScan-derived 'visceral fat' and MRI-derived IAAT similar to that reported in the developmental studies of the ViScan against computed tomography (Yamaguchi et al, 2006); however, waist circumference alone explained more of the variance in our cohort.…”
Section: Discussionsupporting
confidence: 82%
“…The idea that transimpedance is influenced by fat content of the mesentery (that is, IAAT) was first suggested by Scharfetter et al (2005). Our study showed a strong relationship between ViScan-derived 'visceral fat' and MRI-derived IAAT similar to that reported in the developmental studies of the ViScan against computed tomography (Yamaguchi et al, 2006); however, waist circumference alone explained more of the variance in our cohort.…”
Section: Discussionsupporting
confidence: 82%
“…(iii) Waist circumference: Nonextensible steel tapes (KDSW-2008) were used to assess waist circumference, which was measured level with the umbilicus to standardize the procedure. (iv) Body composition: Percentage body fat, fat mass (FM) and fat-free mass (FFM) were determined using the Imp™ SFB7 bioelectrical impedance (BIA) analyzer (Moon et al, 2008, Scharfetter et al, 2005. The Imp™ SFB7 is a multifrequency, tetra-polar bioelectrical impedance spectroscopy (BIS) device (Nielsen et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…When using non-invasive approaches, arterial, venous, and other fluid components may send overlapping signals to the surface. Impedance methodologies do not allow for reliable distinction of signals caused by fluid shifts within (intravascular), outside of (extravascular), or between (filtration) extracellular fluid spaces (Segal et al 1991;Lozano-Nieto and Turner 2001;Scharfetter et al 2005). Developments in mini-invasive pressure monitoring (Della Rocca et al 2008) may offer future paths for experimental observations into the dynamics of hydrostatic indifference locations in humans.…”
Section: Non-invasive Determination Of Hydrostatic Indifference Locatmentioning
confidence: 99%